Advances in magnetic field approaches for non-invasive targeting neuromodulation - Alipour, Mozhgan; Abdolmaleki, Maryam; Shabanpour, Yaser; Zali, Alireza; Ashrafi, Farzad; Nohesara, Shabnam; Hajipour-Verdom, Behnam (Frontiers in Human Neuroscience, 2025)
Neuromodulation, the targeted regulation of nerve activity, has emerged as a promising approach for treating various neurological and psychiatric disorders. While deep brain stimulation has shown efficacy, its invasive nature poses substantial risks, including surgical complications and high costs. In contrast, non-invasive neuromodulation techniques, particularly those utilizing magnetic fields (MFs), have gained increasing attention as safer, more accessible alternatives. Magnetothermal stimulation has emerged as an innovative method that enables precise modulation of neuronal ion channels through localized heating induced by interaction of MF with biological tissues. This review discusses the principles of MF-based neuromodulation and highlights the critical role of ion channels in synaptic transmission, and the therapeutic potential of these advanced techniques. Additionally, it highlights key challenges such as spatial targeting precision, safety considerations, and the long-term effects of magnetic exposure on brain function. The findings presente the promise of MF-based neuromodulation as a non-invasive, highly targeted therapeutic strategy for conditions such as epilepsy, movement disorders, and neurodegenerative diseases, with potential applications in chronic pain management and future clinical interventions.